(3QSGdI aj EjVGM hLO Cf jYGO eG Hjf GdfGXQ heQGcR CYeOI GdLHGd hYdh CYeOJgG hYde Yeb GdBHGQs - (3jYbhH Hf ESMGb, CHh jhSa, GHf GdScjJ,J (B224 (3g` s
(3ChdgG (B:s
(3CeG HYO ai edc Gddg JUfYg hGjOc HJhajbg Ef GdPi JSCdJ Yfg ef GdMjdI ai GdHYO GdPi ef YdGeI eaQhVI hHjf eQcR Yeh LHd eaQhV s
(3BNQgG (B:s
(3abOQ GM` YfO C H eYdhe dGf M` C eYdhe hPdc eG CQOfG Cf fHjf cedJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeS hGdYTQhfs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B243 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B536s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs